Ascitic Fluid in Ovarian Mass with Special Reference to Paired-box Gene 8 Immunoexpression: A Cross-sectional Analysis - Prabhat Mahato; Chhanda Das; Rama Saha; Ankita Pranab Mandal; Gourisankar Kamilya (International Journal of Advanced Medical and Health Research)
Introduction: Mortality in the case of ovarian malignancy is high due to late diagnosis. Early and accurate diagnosis can improve case-specific management. Paired-box gene 8 (PAX8) has proved to be expressed in the ovarian epithelial cells and is considered a new biomarker for early diagnosis. Case–control studies show that the level of PAX8 in the serum and tissue expressions are positively correlated and increased in ovarian malignancy, especially in the high-grade serous type, the most common variety of ovarian malignancies. Aims: The aim of this study was to assess the epidemiological spectrum of ovarian neoplastic lesions and a comparative study of conventional cytology and a cellblock of ascitic fluid and subsequent PAX8 immunohistochemistry (IHC) expression to diagnose ovarian neoplasm. Materials and Methods: We collected clinical data from participants using a predesigned pro forma. We made a cytological diagnosis using conventional cytology, followed by cellblock preparation and subsequent assessment of PAX8 IHC expression. Ascitic fluid received for cellblock was centrifuged, tissue sediment was mixed with plasma, and then drops of thrombin were added. We fixed the clotted sample by adding 10% formalin for 30 min. The formalin-fixed, paraffin-embedded cellblocks were sliced into 4–5 μ sections and stained with hematoxylin and eosin. Subsequently, we used an immunohistochemical stain for PAX8 expression to diagnose ovarian malignancy. Results: We received 55 ascitic fluid samples. On cytological smear examination, 12 (21.8%) cases were benign, 35 (63.6%) were malignant, and the remaining 8 (14.6%) were suspicious of malignancy. On histological examination of cellblock preparation, 43 (78.2%) were malignant cases, and among these 43 cases of cellblocks studied, 37 were positive for PAX8 status; six were negative for PAX8. There was a statistically significant association between malignant cell positivity and PAX8 status in the cellblock (P < 0.001). Conclusion: An evaluation of PAX8 status in ascitic fluid cellblock study should be considered for high-grade ovarian cancers in patients who may benefit from targeted therapies. Patients with ovarian mass and ascites can be evaluated for PAX8 status in their ascitic fluid cytology study for the purpose of neoadjuvant chemotherapy.